Haunted futures: The stigma of being a mother living apart from her child(ren) as a result of state-ordered court removal. Issue 4 (July 2018) - Morriss, Lisa
The notion of 'haunted futures' can provoke new understandings of the experiences of birth mothers living apart from their children as a result of state-ordered court removal. As 'abject figures', the mothers are silenced through the stigma and shame of being judged to be a deeply flawed mother, the justifiable fear of future children being removed, and court-ordered reporting restrictions. In this article, the author depicts how these mothers exist in a state of haunted motherhood : they are paralysed in anticipation of an imagined future of reunification with their children. The mothers are painfully aware that any future pregnancy will also be subject to child protection procedures; thus even their future motherhood continues to be stigmatised by the past. However, while the ghosts of removed children signify a traumatic loss, they also simultaneously represent hope and future possibilities of transformation through re-narrativisation. The creation of spaces for the mothers to speak about their experiences can foster a 'maternal commons'. This ending of enforced silencing can be a political act, countering the stigma caused by pathologising individual mothers and making visible how structural inequalities and governmental policies impact on the lives of the most vulnerable families in the UK.